2014
DOI: 10.1097/qad.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Decline in locomotor functions over time in HIV-infected patients

Abstract: Compared to published data from healthy persons of similar age, baseline 5STS time and 6MWD were poorer in HIV-infected adults and associated with subsequent falls. Test performances deteriorated further over time. Age, diabetes, neurologic complications and injection drug use, rather than virologic factors, contribute to variations in lower limb muscle performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 35 publications
3
53
1
6
Order By: Relevance
“…The characteristics of our population differed from those of Richert et al [5]. Our sample was predominantly female (67.53%) and the median age was 45.4 years, whereas the Bordeaux team studied a group consisting of 80% men with a median age of 47.6 years (IQR=41.8-53.9) [5,13,14]. Most studies show that the prevalence of these disorders is directly related to age [2,9,10].…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The characteristics of our population differed from those of Richert et al [5]. Our sample was predominantly female (67.53%) and the median age was 45.4 years, whereas the Bordeaux team studied a group consisting of 80% men with a median age of 47.6 years (IQR=41.8-53.9) [5,13,14]. Most studies show that the prevalence of these disorders is directly related to age [2,9,10].…”
Section: Discussioncontrasting
confidence: 43%
“…We therefore found a significant association between performance in the "five-times sit-to-stand" test and duration of HIV infection, but no relation with either immuno-virological characteristics nor duration of exposure to antiretrovirals [12,14]. Richert et al found that age, the presence of diabetes, cerebral complications related to AIDS and drug use were risk factors for the development of locomotors disorders [13].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, HIV-infected older persons on virologically suppressive antiretroviral therapy demonstrated significantly diminished physical function compared to similarly aged persons without HIV infection, putting them at risk for falls and mobility-related disability [2628]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that impaired locomotor function, as determined by routine functional tests of the lower extremities, is both common and increases over time in older HIV patients with comorbidities [92, 93]. This is an important risk for falls and interacts closely with the decline in gait speed which also occurs in older HIV patients [94].…”
Section: Frailty and Physical Function Impairment As Risks For Low Bmmentioning
confidence: 99%